No apparent genetic bottleneck in the demographically declining European eel using molecular genetics and forward-time simulations - Pujolar, JM; Bevacqua, D; Andrello, M; De Leo, GA; Zane, L.; CAPOCCIONI, FABRIZIO; CICCOTTI, ELEONORA (Conservation Genetics, 2011)
No apparent genetic bottleneck in the demographically declining European eel using molecular genetics and forward-time simulations.